Implementing of Kinematic Synergy Strategies to Develop basic Language Skills for A Sample of Special Needs Students - Zhran, Dr. Ayman Ramadan Soliman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop the basic skills of the Arabic language (listening- speaking - reading - writing) by providing visual and motor synergy skills to a sample of students with educational concerns. The sample included (35) students of both males and females in the intermediate education stage who suffer from learning difficulties and excess Minor distraction, hearing and visual impairment. The study adopts the semi- experimental approach that depends on the same group and the application before and after the same group, and the researchers prepared a measure of the Arabic language skills that included the four basic skills and its validity and stability were verified, and the results of the study indicated a noticeable improvement in the four skills when comparing the averages of grades before and after, This indicated the effectiveness of visual and motor synergy strategies to develop basic Arabic language skills among students of interest.